Effectiveness of Neurodynamic Sliding Stretching Technique on Flexibility in Males with Short Hamstrings - Anuradha Lehri; Harshita Yadav (International Journal of Pharma and Bio Sciences, 2021)
The short hamstring is one of the major contributing factors which are associated with musculoskeletal injuries in adolescents and adults. The study aims to find the effectiveness of Neurodynamic Sliding (NDS) technique on hamstring and back flexibility in males with short hamstrings. A total of 136 eligible subjects were divided into two groups (Group A = 68 and Group B = 68). The subjects included were only males with age range 20-24 years, subjects with bilateral short hamstrings with knee extension angle (KEA) ≤160 degree with hip flexion at 90 degree, BMI within range 20 kg/m2 to 24.9 kg/m2 will be included to keep homogeneity in body type. The exclusion criteria comprise of subject with recent hamstring injury, verbal report of performing regular lower extremity muscle stretching and exercises, with the history of fracture in any part of body, with history of growth disorders, history of any neurological or orthopedic conditions. Group A (Experimental) subjects were given NDS 5 times on 5 consecutive days. Whereas, the subjects in group B (Control) were not given any treatment. The outcomes measures were Straight leg raise (SLR), Knee extension angle (KEA), and Sit and reach test (SRT) for dominant and non-dominant leg side. The finding showed that there was statistically significant improvement (p≤ 0.05) in SLR, KEA and SRT in Group A after giving NDS for 5 days as compared to the subjects in Group B (Control conditions). The study concludes NDS proved to be an effective technique in improving hamstring and back flexibility in male subjects with short hamstrings.